Religiosity and emotional intelligence on Muslim student learning achievement - Fikri Farhan; M. Abdul Rofi’ulmuiz (International Journal of Evaluation and Research in Education (IJERE), 2021)
Learning achievement was one of the indicators often used to measure student success in learning. A comprehensive understanding of this topic requires contributions from a variety of disciplines. Recently, researchers are interested in examining the impact of religiosity and emotional intelligence on learning achievement. However, the study on this topic is inconclusive. This study aimed to examine the influence of religiosity and emotional intelligence on learning achievement by learning motivation as a mediating variable. This research was conducted with a quantitative approach. The data was collected through a questionnaire distributed to 122 students of the Management study program, Faculty of Business and Economics, Islamic University of Indonesia. The data was processed using SPSS analysis tools with hierarchical regression analysis techniques. The results demonstrated religiosity and emotional intelligence had a positive impact on learning motivation; learning motivation positively impacted learning achievement. Furthermore, learning motivation mediated the correlation between religiosity and emotional intelligence on learning achievement. The results offer practical implications for campus leaders; Campus leaders should instill religiosity and emotional intelligence in Muslim students to improve their learning achievement.